2015
DOI: 10.1159/000371580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1,2,3,4-Tetrahydroisoquinoline Derivatives on Dopaminergic Spontaneous Discharge in Substantia Nigra Neurons in Rats

Abstract: 1,2,3,4-Tetrahydroisoquinoline (TIQ) and its derivatives, 1-methyl-TIQ (1-MeTIQ) and 1-benzyl-TIQ (1-BnTIQ), are endogenously present in the human brain. In this study, we compared the effects of TIQ derivatives on spontaneous nigral dopaminergic discharge in rats treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). In the low-to-middle dose range (0.01-1 mg/kg), intravenous administration of MPTP induced a transient and potent increase in the firing rate. TIQ (0.01-30 mg/kg) had no effects, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A great deal of the experimental evidence demonstrates that oxidative stress is a principal reason of cell death and that an abnormal concentration of reactive oxygen and nitrogen species leads to the damage of a lot of lipids, proteins and also DNA. As reported by Antkiewicz-Michaluk and collaborators (Antkiewicz-Michaluk et al 2014), 1-MeTIQ possesses neuroprotective actions, probably attributable to its ability to reduce oxidative stress Wąsik and Antkiewicz-Michaluk 2017) by free radicals scavenging, prevention of cell membrane deterioration and glutamate-induced excitotoxicity inhibitory events Chiba et al 2015). Antkiewicz-Michaluk et al (2014) also demonstrated that 1-MeTIQ through MAO inhibition might play an essential role in neuroprotection confirming the important role of catecholamines in the formation of TIQs ).…”
Section: -Metiqmentioning
confidence: 57%
See 1 more Smart Citation
“…A great deal of the experimental evidence demonstrates that oxidative stress is a principal reason of cell death and that an abnormal concentration of reactive oxygen and nitrogen species leads to the damage of a lot of lipids, proteins and also DNA. As reported by Antkiewicz-Michaluk and collaborators (Antkiewicz-Michaluk et al 2014), 1-MeTIQ possesses neuroprotective actions, probably attributable to its ability to reduce oxidative stress Wąsik and Antkiewicz-Michaluk 2017) by free radicals scavenging, prevention of cell membrane deterioration and glutamate-induced excitotoxicity inhibitory events Chiba et al 2015). Antkiewicz-Michaluk et al (2014) also demonstrated that 1-MeTIQ through MAO inhibition might play an essential role in neuroprotection confirming the important role of catecholamines in the formation of TIQs ).…”
Section: -Metiqmentioning
confidence: 57%
“…Most of the TIQs found in the brain are nowadays commonly recognized as endogenous neurotoxins with neurochemical properties similar to those of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), the also structurally similar compound most famous for causing Parkinson's disease (PD) (Herraiz 2016). Interestingly, as it occurs with MPTP, important differences may be related to the enzymes involved in the mechanisms of toxicity (Herraiz 2016); in particular, TIQs can be metabolically activated by conversion into potentially toxic substances, although one of the most striking differences with respect to MPTP refers to the fact that TIQsinduced neurotoxicity is relatively weaker compared to that induced by MPTP (Chiba et al 2015). Notably, MPTP and its oxidation by-product, 1-methyl-4-phenylpyridinium cation (MPP + ), are selective DArgic neurotoxins that when administered directly into the mice brain induce neuronal degeneration that can provide the experimental animal models of parkinsonism extensively used to investigate the mechanisms underlying neurotoxicity and neurodegeneration as well as to find drugs able to exert neuroprotective effects against oxidative stress-mediated neurotoxicity (Chiueh et al 1984;Jackson-Lewis and Przedborski 2007).…”
Section: Tetrahydroisoquinolinesmentioning
confidence: 99%